The influence of learners' textbooks on Sepedi writing skills in a grade 7 classroom : a case of primary schools in Lebowakgomo Circuit - Ngobeni, Nkame Emmanuel (My University, 2023)
The aim of the study was to investigate the influence of learners’ textbooks on Sepedi essay writing skills. Grade 7 learners at primary schools in Lebowakgomo Circuit are faced with challenges of language proficiency due to unnecessary usage of loaned words, orthographic and morphological errors in their written essays. This study adopted qualitative approach and followed a case study design and an interpritivist paradigm. Qualitative data was collected through semi-structured interviews and document analysis of the learners’ textbooks and written essays. Data collected was analysed following the inductive method of thematic data analysis. The research highlighted that learners use Sepedi textbooks that contain spelling errors, infusion of languages like English, Afrikaans and isiZulu that negatively affect learners’ writing skills. It was evident that the errors in learners’ essays emanated from the textbooks given from the schools. It is recommended that Sepedi Home Language textbooks be thoroughly proofread before being supplied to schools. The Department of Basic Education should ensure that authors of textbooks show a good conduct of the language because home language carries the pride, culture, heritage and identity of the learners they are prescribed for
Thesis (M.Ed. (Language Education)) -- University of Limpopo, 2023
Keywords: Influence of learners'; Textbooks; Sepedi writing skills; Grade 7 classroom; Academic writing -- Ability testing; Language and languages -- Study and teaching; Essay, Writing; Sepedi language -- Textbooks; Spelling errors